Pathologic response at the epicenter of the treatment decision-making process in Human Epidermal Receptor–Type 2 overexpressing (Her2+) Early Breast Cancer (EBC): Challenges and opportunities for financially-constrained healthcare systems. (December 2020) - Mano, Max S.
Abstract: After more than two decades of intensive research, tremendous progress has been achieved in the management of Human Epidermal Receptor-2 overexpressing (Her2+) Early Breast Cancer (EBC). In the latest years, major clinical trials have explored the neoadjuvant scenario, in addition to the prognostic role of pathologic complete response (pCR) and the possibility of a 'tumor biology-driven' patient selection provided by the assessment pathologic response. However, the introduction of new agents has been a major burden for financially-constrained healthcare systems–which includes those from most emerging markets (currently representing 85% of the world population) but also, to some extent, public systems from welfare states. This manuscript addresses evidence-based opportunities to promote a more rational utilization of the available resources in Her2+ EBC, in addition to areas of interest for future research in cost-efficiency. Highlights: Major progress has been achieved in the management of Her2+ Early Breast Cancer. The neoadjuvant setting and pathologic response have been widely explored in trials. Financially-constrained healthcare systems have struggled to introduce new agents. There are opportunities to promote a more rational utilization of the resources. Financially-constrained healthcare systems should focus on cost-efficiency research.